Rome and the Worlds beyond its Frontiers - Slootjes, Daniëlle; Peachin, Michael (Impact of Empire, 2016)
Rome and the Worlds Beyond Its Frontiers examines interactions between those within and those beyond the boundaries of Rome, with an eye to the question of contested identities and identity formations. Readership: All interested in the history of the Roman Empire, and its relationships with those beyond its borders.